Pulmonary candidiasis in cystic fibrosis. Issue 7 (July 1979) - Jenner, B M; Landau, L I; Phelan, P D
Abstract : A child with cystic fibrosis and asthma developed pulmonary candidiasis. Predisposing factors in this patient were prolonged antibiotic therapy, high-dose corticosteroids, and intravenous catherisation. A diagnosis was made by lung puncture and confirmed by rapid response to 5-fluorocytosine.